Measurement of socio‐economic status in families of children with cancer in Guatemala. Issue 11 (19th April 2014) - De Pernillo, M.; Rivas, S.; Fuentes, L.; Antillon, F.; Barr, R.D.
Abstract The prospects for survival of children in low and middle income countries are linked to their families socio‐economic status (SES), of which income is only one component. Developing a comprehensive measure of SES is required. Informed by clinical experience, a 15‐item instrument was designed in Guatemala to categorize SES by five levels in each item. Almost 75% of families attending the Unidad Nacional de Oncología Pediátrica were in the lowest three of six categories, providing a framework for stratified financial and nutritional support. The measure of SES offers an opportunity for examining associations with health outcomes throughout Latin America. Pediatr Blood Cancer 2014;61:2071–2073. © 2014 Wiley Periodicals, Inc.